The Medieval Saga - Clover, Carol J., 1940- (Book collections on Project MUSE., 2019)
Written in the thirteenth century, the Icelandic prose sagas, chronicling the lives of kings and commoners, give a dramatic account of the first century after the settlement of Iceland--the period from about 930 to 1050. To some extent these elaborate tales are written versions of traditional sagas passed down by word of mouth. How did they become the long and polished literary works that are still read today?The evolution of the written sagas is commonly regarded as an anomalous phenomenon, distinct from contemporary developments in European literature. In this groundbreaking study, Carol J. Clover challenges this view and relates the rise of imaginative prose in Iceland directly to the rise of imaginative prose on the Continent. Analyzing the narrative structure and composition of the sagas and comparing them with other medieval works, Clover shows that the Icelandic authors, using Continental models, owe the prose form of their writings, as well as some basic narrative strategies, to Latin historiography and to French romance.